2017
DOI: 10.5114/kitp.2017.66922
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory functional status after conventional and minimally invasive aortic valve replacement surgery – a propensity score analysis

Abstract: IntroductionReports describing respiratory function of patients after conventional or minimally invasive cardiac surgery are infrequent.AimTo compare pulmonary functional status after conventional (AVR) and after minimally invasive, through right anterior minithoracotomy, aortic valve replacement (RT-AVR).Material and methodsThis was an observational analysis of 212 patients scheduled for RT-AVR and 212 for AVR between January 2011 and December 2014 selected using propensity score matching. Respiratory functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Six studies ( 5 , 6 , 14 16 , 35 ) reported on postoperative respiratory function tests based on spirometry, revealing that the overall complications were significantly reduced with MIVS compared to FS (964 vs. 964, WMD −24.83 95% CI [−29.90, −19.76]; p = <0.00001). Most pulmonary function tests showed that the MIVS group had better respiratory function than the FS group 1 week after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies ( 5 , 6 , 14 16 , 35 ) reported on postoperative respiratory function tests based on spirometry, revealing that the overall complications were significantly reduced with MIVS compared to FS (964 vs. 964, WMD −24.83 95% CI [−29.90, −19.76]; p = <0.00001). Most pulmonary function tests showed that the MIVS group had better respiratory function than the FS group 1 week after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Our experience supports this, with only four patients requiring transfusion of pRBCs postoperatively and we believe sparing the sternum greatly contributes to this low incidence. The risk of renal and respiratory failure has also been found to be lower in RAMT AVR cohorts when compared to sternotomy approaches, both full and hemi‐sternotomy 50,55 . In our study, no patients experienced postoperative kidney injury that necessitated intervention (continuous renal replacement therapy or dialysis).…”
Section: Discussionsupporting
confidence: 50%
“…The risk of renal and respiratory failure has also been found to be lower in RAMT AVR cohorts when compared to sternotomy approaches, both full and hemi-sternotomy. 50,55 In our study, no patients experienced postoperative kidney injury that necessitated intervention (continuous renal replacement therapy or dialysis). Studies have also found RAMT AVR is associated with shorter ventilatory times.…”
Section: Postoperative Outcomesmentioning
confidence: 70%
“…Sternal integrity is crucial for faster respiratory recovery, early hospital discharge and physical functioning [15]. The physical functioning scale includes daily activity, including the ability to engage in vigorous activities such as running and weightlifting, to perform moderate activities or to carry groceries, to climb several flights of stairs, to walk several blocks, to bend, and to kneel, all of which are related to sternal stability.…”
Section: Discussionmentioning
confidence: 99%